Bamboo-kenaf fibers reinforced PLA composites: Enhancing moisture control, surface wettability, and flame resistance for eco-friendly packaging and furniture - Khan, Abir; Sapuan, S.M.; Zainudin, E.S.; Zuhri, M.Y.M. (Elsevier, 2025)
The growing environmental concerns over non-biodegradable plastics have spurred the need for sustainable alternatives. While, natural fiber-reinforced PLA composites offer promise, they often suffer from poor moisture resistance, weak adhesion, and flammability. This study explores bamboo-kenaf/PLA hybrid composites (30:70, 50:50, 70:30 ratios) and non-hybrid variants (bamboo-PLA, kenaf-PLA) to address these limitations. The results showed that kenaf-PLA exhibits the highest moisture uptake (enhanced biodegradability) and lowest water vapor permeability (5.12 × 10−10 gs−1m−1Pa−1), ideal for moisture-sensitive packaging. The 50:50 hybrid composite achieved optimal balance with superior dimensional stability and exceptional hydrophilicity (contact angle: 61.47°), addressing PLA's adhesion challenges. All composites exhibited enhanced fire resistance compared to conventional polypropylene and polyethylene. These findings highlight the potential of bamboo-kenaf/PLA composites as sustainable materials for eco-friendly packaging and furniture applications.